The epidemiology of stifle joint disease in an insured Swedish dog population. (1st March 2021) - Engdahl, Karolina; Hanson, Jeanette; Bergström, Annika; Bonnett, Brenda; Höglund, Odd; Emanuelson, Ulf
Abstract: Background : Stifle joint diseases (SJD) are common in dogs and include a variety of diagnoses. The objective of the study was to provide an overview of the epidemiology of SJD in insured dogs. Methods : An historical single cohort study of dogs insured in Agria Pet Insurance (2011–2016) in Sweden was performed. Incidence and relative risk (RR) of SJD was calculated for the whole dog population and for subgroups divided by breed, breed group and sex. Results : The study population included almost 600, 000 insured dogs (>1.7 million dog‐years). Ninety‐three different stifle joint diagnoses were reported in 9624 dogs, and the most common were cruciate ligament rupture and patellar luxation. The incidence of SJD was 55.4 cases per 10, 000 dog‐years at risk. Bulldog and boerboel had the highest RR of SJD. The breeds that accounted for the highest proportion of all SJD claimed dogs were mixed breed and Labrador retriever. Female dogs had a slightly increased RR compared with male dogs (RR 1.06, p = 0.006). The incidence increased yearly during the observation period. Conclusion : The study demonstrates breed‐specific differences in incidence of SJD in dogs, which may be of importance for breeders, dog owners and veterinarians.